Impact of the α optical model potential on the γ-process nucleosynthesis. (26th April 2017) - Simon, A; Beard, M; Meyer, B S; Roach, B
Abstract: γ -process nucleosynthesis that occurs during an explosion of a type II supernova can be modeled via post-processing network calculations that require a model of the stellar environment and the rates for all the nuclear reactions involved in the process. The nuclear input for these calculations relies on reaction rates obtained from statistical models. In this work, the sensitivity of the γ -process nucleosynthesis to the α optical model potential used in statistical model was investigated. Network calculations were performed for two sets of reaction rates, the current version of Reaclib and with rates for α -induced reactions and their inverse replaced with those calculated using Talys. Significant changes in the final abundance pattern were observed and a list of reactions that need to be measured in order to discriminate between the two nucleosynthesis scenarios is provided.